Pengelolaan Limbah Medis Padat Di Rumah Sakit Umum Daerah Mamuju Provinsi Sulawesi Barat - Amelia, Andi Rizki; Ismayanti, Annisa; Rusydi, Arni Rizqiani (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
The hospital as an institution whose task is to provide health services to the community, is inseparable from the responsibility for the health of the surrounding environment, namely managing medical waste properly (as required). The purpose of this study is to determine the management of solid medical waste in the Mamuju District General Hospital, West Sulawesi Province in 2019. The type of research used is observational with descriptive approach, the population is all rooms that are included in the medical category and the sample is all populations that are used the sample. Sampling will use a total sample system (exhaustic sampling). Processing and analyzing the observational data is then processed manually and grouped according to purpose. The results showed that sorting, storage, transportation, temporary shelter and final disposal site did not meet the requirements in accordance with the Republic of Indonesia Decree No. Kepmenkes. 1204 / Menkes / SK / X / 2004, because some rooms have not been sorted out medical or non-medical waste even though the container has been prepared according to the type of waste, the container is difficult to clean and empty because some containers are not equipped with plastic bags, the transport process uses lines general so that disrupt hospital activities. In addition, the hospital waste temporary shelter only has a 4 x 4 room located behind the hospital and does not separate medical and non-medical waste. Hospital waste disposal equipment is not used because it does not yet have an operational permit. The conclusion of the research is that the management of solid medical waste in hospitals has not yet met the requirements. It is recommended that the implementation of management runs well, required standard operating procedures on how to manage waste at the source, training on waste sorting techniques according to its type and obtaining an operation permit for the use of an incinerator